Daya Saing Tujuan Wisata: Kajian Pustaka Sistematis - Khaeril Khaeril; Mahlia Muis; Jusni Jusni; Madris Madris (Lasigo Akademia Indonesia, 2020)
This article aims to discuss the current research trends on the tourism destination competitiveness. This research is sistemic literature review by using Publish or Perish software for data mining and VOSviewer for data analysis and visualization. The results indicate 4 research cluster themes on tourism destination competitiveness and 5 research clusters related to tourism destination competitiveness. The main cited articles on tourism destination competitiveness for period of 2005-2020 are Larry Dwyer, Chulwo Kim, Tanja Mihalic, Tanja Amenski, Vanja Dragineva, and Ugljesa Stankov. Based on the research findings, we state that the research gaps in the tourism destination competitiveness are still wide open, particularly in Indonesia.